Power in Economic Thought (Palgrave Studies in the History of Economic Thought,, 2018)
This book offers a pluralistic vision of the way economists have dealt with the question of power in society over the last two centuries. Economists' ideas about power are examined from political, theoretical and policy-making points of view, with additional discussion of the active participation of economists in the management of power. The book is organized into four main conceptions of power relations: i) Power as embedded in political institutions; ii) Power as emerging from the asymmetric relations caused by the unequal distribution of income and wealth; iii) Power as associated to the monopolistic or oligopolistic position held by some firms in the market; and iv) Power as the management of economic policies by the state. Mosca brings together contributions from a range of scholars to analyse how economists have considered the role of power, putting the discussion into a much needed historical context. Manuela Mosca is Professor of History of Economic Thought in the Department of Economics, University of Salento, Italy and Visiting Professor at the University of Bologna, Italy. She is a member of the International Advisory Board of the European Journal of the History of Economic Thought and of the Editorial Board of History of Economic Theory and Policy. Her main research interests are the history of the theory of monopoly power and marginalism in Italy.